2011
DOI: 10.1021/bm1014365
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalization of TiO2 Nanotubes with Bone Morphogenetic Protein 2 and Its Synergistic Effect on the Differentiation of Mesenchymal Stem Cells

Abstract: To investigate the influence of surface-functionalized substrates with nanostructures on the behaviors of mesenchymal stem cells, we conjugated bone morphogenetic protein 2 (BMP2) onto TiO(2) nanotubes with different diameter sizes of 30, 60, and 100 nm for in vitro study. Polydopamine was employed as the intermediate layer for the conjugation of BMP2. The successful conjugation of BMP2 onto TiO(2) nanotubes was revealed by field-emission scanning electron microscopy (FE-SEM), X-ray photoelectron spectroscopy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

7
140
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 235 publications
(149 citation statements)
references
References 50 publications
7
140
0
2
Order By: Relevance
“…28 Briefly, MSC were incubated with TiO 2 particles (0.10 mg/mL) for 15 days at an initial seeding density of 5 × 10 4 cells/cm 2 . The cells were washed with phosphate-buffered solution and fixed with 2% glutaraldehyde at 4°C for 20 minutes.…”
Section: Mineralizationmentioning
confidence: 99%
“…28 Briefly, MSC were incubated with TiO 2 particles (0.10 mg/mL) for 15 days at an initial seeding density of 5 × 10 4 cells/cm 2 . The cells were washed with phosphate-buffered solution and fixed with 2% glutaraldehyde at 4°C for 20 minutes.…”
Section: Mineralizationmentioning
confidence: 99%
“…22 The formation of focal adhesion contacts and cell adhesion is an important starting point for cell proliferation, differentiation, and some cellular behaviors, which is activated by the formation of vinculin adhesion spots. 23,24 The higher expression exhibited better adhesion. It has been reported that various kinds of physical stresses can accelerate stem cell differentiation into specific cells.…”
mentioning
confidence: 99%
“…[20][21][22] In addition, as another non-canonical amino acid, phosphonated serine has been applied to underwater adhesion. [23][24][25] Such phosphate groups have been found in the underwater adhesive proteins of the sandcastle worm and caddy silks, 16,17 which interact specifically with a titanium surface.…”
mentioning
confidence: 99%